Modeling the Electricity Generation Processes of a Combined Solar and Small Hydropower Plant - Mykola Dyvak; Volodymyr Manzhula; Andriy Melnyk; Nataliia Petryshyn; Tiande Pan; Arkadiusz Banasik; Piotr Pikiewicz; Wojciech M. Kempa (Energies)
This article proposes the concept of an integrated system consisting of two components: a small hydropower plant (SHPP) and a solar power plant (SPP), where the SHPP operates as a pumped-storage hydropower plant, and the SPP supplies energy for lifting water to the upper reservoir. A methodology is proposed for evaluating the joint operation of a solar power plant and a small hydropower plant. The methodology is based on modeling the electricity generation processes of combined solar and small hydropower plants. Additionally, a novel hybrid method is proposed for identifying interval models of small hydropower plants (SHPPs) and solar power plants (SPPs). This method integrates a metaheuristic algorithm for model structure synthesis, inspired by the behavioral model of a bee colony, with gradient-based methods for parameter identification. Using the proposed method, interval models have been developed for both small hydropower plants and the electricity generation of solar power plants. This study confirms the feasibility of using interval models to describe the relationship between electricity generation in a small hydropower plant and factors such as head difference, reactive power, and water level in the reservoir (i.e., available water resources). Furthermore, a mathematical model in the form of a difference equation is used to describe the daily electricity generation of a solar power plant. This model accounts for the characteristics of compressors that pump water from the lower to the upper reservoir. Based on the developed models, an assessment is conducted on the efficiency of the pumped-storage SHPP in ensuring operational stability during peak loads in the power grid and addressing seasonal variations.